2006
DOI: 10.1007/s00280-006-0370-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hyperfractionation and conventional fractionation radiotherapy with concurrent docetaxel, cisplatin and 5-fluorouracil (TPF) chemotherapy in patients with locally advanced squamous cell carcinoma of the head and neck (SCCHN)

Abstract: There were trend toward improved local-regional control, disease-free survival and overall survival in Hfx RTx with concurrent TPF CTx, compared to Cfx RTx with concurrent TPF CTx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The specific regimens were induction chemotherapy consisting of CDDP, docetaxel (DOC) and 5-fluorouracil (5-FU); radical therapy consisting of CDDP, DOC, and 5-FU in combination with radiotherapy [7][8][9]; and postoperative therapy using CDDP in combination with radiotherapy. In the induction chemotherapy, CDDP and DOC were both administered at 60 mg/m 2 on day 1 and 5-FU at 800 mg/m 2 from day 1 to day 5.…”
Section: Methodsmentioning
confidence: 99%
“…The specific regimens were induction chemotherapy consisting of CDDP, docetaxel (DOC) and 5-fluorouracil (5-FU); radical therapy consisting of CDDP, DOC, and 5-FU in combination with radiotherapy [7][8][9]; and postoperative therapy using CDDP in combination with radiotherapy. In the induction chemotherapy, CDDP and DOC were both administered at 60 mg/m 2 on day 1 and 5-FU at 800 mg/m 2 from day 1 to day 5.…”
Section: Methodsmentioning
confidence: 99%
“…The radiosensitizing potential of docetaxel has been explored in vitro, in vivo and in clinical trials (5,6,26,27). However, several reports have shown that docetaxel resistance depends on redox regulation, as mediated by increased expression of TRX and a reduction in ROS generation (28).…”
Section: Discussionmentioning
confidence: 99%
“…This percentage is very much higher than that of other studies and, probably, would have had a negative impact on the response rate and OS. Secondly, the concurrent schedule differs signifi cantly from trials evaluating concurrent taxanes and radiotherapy [11,12,14,[21][22][23][24]. For example, Matsumoto et al published the results of a study in 25 patients with advanced H&N treated with weekly docetaxel (10 mg/m 2 ) and hyperfractionation radiotherapy (72 Gy at 1.2 Gy twice daily).…”
Section: Discussionmentioning
confidence: 97%